Percepção de adolescentes escolares sobre o uso do celular - Borges, Silvani Weber da Silva (2021)
Objective: To understand the perception of school adolescents about the use of cell phones. Method: Qualitative descriptive and exploratory study involving 17 adolescents between 14 and 18 years of age in the city of Foz do Iguaçu. Data collection was performed through semi structured changes using the snowball. The data were formed using the Content Analysis framework in the thematic modality. The information occurred during the months of July and August 2020. Results: The speech of adolescents about their perception of cell phone use reveals that this device represents all the freedom they need to access what they want from where forced, with autonomy to seek matters of interest to them without adult approval. In addition, in the teenagers' perception, the cell phone represents a safe haven, with which they feel they are never alone. As for the relationship, the adolescents admit that they usually use the cell phone for a long period and with frequent cell phone checks during the day or night, not respecting the hours of study, food or rest. They also report that, although they use the cell phone predominantly to access social networks and games, they also use it to search for information of interest and remain specialized. As a motivation for the excessive use of cell phones, adolescents listed loneliness, boredom, everyday tensions, the need to belong and family absence as the most relevant. Of the strategies to reduce the use of cell phones, adolescents pointed out the dialogue as a central factor to prevent the excessive use of technologies, whether within the family, with greater interaction between parents and children, or in no school environment, through agreements between teachers and students regarding the use of cell phones. This work also presented an integrative literature review in which eighteen scientific articles were analyzed. Related productions had as main effects of excessive use of the cell phone, sleep disorders, anxiety, depression, loneliness, distraction, as well as a higher risk for suicide. Regarding the evidence, self-esteem, social support and family and peer relationships were the most important motivations for the excessive use of cell phones by adolescents. Regarding the possibilities of coping, only one article was found, in which it showed the importance of involving the family and the school in the prevention of cell dependence in adolescents. Final considerations: The present work can help in the construction of knowledge to understand the adolescents' perception and relationship with the cell phone, in addition to knowing the main motivations for excessive use and, thus, thinking about prevention objectives. In this sense, this work also sought to arouse the interest of nurses and other health professionals for a comprehensive look at this portion of the population, which little seeks health services, but which presents several risk factors that affect their well-being and their health. healthy development.